Β-carotene isolated from the marine red alga, Gracillaria sp. potently attenuates the growth of human hepatocellular carcinoma (HepG2) cells by modulating multiple molecular pathways. (January 2019) - Kavalappa, Yogendra Prasad; Udayawara Rudresh, Deepika; Gopal, Sowmya Shree; Haranahalli Shivarudrappa, Arpitha; Stephen, Nimish Mol; Rangiah, Kannan; Ponesakki, Ganesan
Graphical abstract: Highlights: Beta-carotene at low concentrations effectively inhibits the growth of HepG2 cells. Its inhibitory effect is linked with altered cell survival, redox and apoptosis signals. Dietary levels of β-carotene might be more advantageous in preventing liver cancer. Abstract: There remains a remarkable controversy on the anti-cancer stand of β-carotene specifically when high concentrations are used. This study aimed to examine the growth inhibitory effect of the lower concentrations of β-carotene in HepG2 cells. Beta-carotene purified from Gracillaria sp. inhibited viability of HepG2 cells in a concentration-dependent manner. This growth inhibitory effect was well correlated with increased apoptotic cell death. Apoptosis induction by β-carotene was associated with increased caspase-3 activity and reduced mitochondrial membrane potential. Western blot analysis showed a significant decrease in the expression of Bcl-2, PARP, and NF-kB protein, and an increase in the protein expression of Bax. Beta-carotene also blocked the activation of intracellular growth signaling proteins, Akt and ERK1/2. Further, it down-regulated the expression of endogenous antioxidant enzymes, SOD-2 and HO-1, and its transactivation factor, Nrf-2. The current study emphasizes the role of β-carotene as an effective inhibitor of the growth of hepatocarcinoma cell.